Science is, sometimes, political - Stevens, Craig (New Zealand Science Review, 2017)
​ The New Zealand Association of Scientists (NZAS) is deeply concerned by the impact of the new US administration. ‘We’ve just gone two weeks with the new US administration and we are witnessing a geopolitical shakeup that is without precedent’, said NZAS President Craig Stevens. ‘The rise of social media has reduced the time for a community to respond to an event down to mere minutes. At the same time, communities are both many - and global. The radical changes being made by the Trump administration ripple across the globe in the blink of a smart-phone.’ As an independent body seeking to promote science, the NZAS has six main aims (www.scientists.org.nz) – each one is and will be impacted by the radical changes being wrought by one of the planet’s dominant nations. This dominance feeds through into economic influence, migration, regional stability and science. We seek to promote science in New Zealand. Science is now global, scientists come from all-over and go all-over. We collaborate, we consolidate, we share knowledge, we discover – globally. The world would not be sure that the climate is changing rapidly due to greenhouse gas emissions without the efforts of scientists of all nationalities. Science and the scientific community cannot tolerate discrimination against people on the basis of their place of birth or religion. In fact, the Trump Administration’s travel ban has horrified the global scientific community. This ban is completely immoral in the context of the current international refugee crisis. It will also retard scientific progress in the United States and the rest of the world at just the time when our civilisation needs science the most. We seek to increase public awareness of science and expose pseudo-science. The US Administration is using new, and seriously partisan, media to deconstruct science. It’s happened before with abhorrent consequences. We debate and influence government science policy. With science being central to so many aspects of our lives, in particular those that we all have in common such as climate and health, these debates cross borders. We seek to improve working conditions for scientists, including gender and ethnic equality. This is completely central to societal advances of the last decade, largely facilitated by global communications and social media, enabling battles to be fought and won with contributions from all over the planet. And these fighters seek open knowledge, transparency, justice, and quality of life for all. We promote free exchange of knowledge and international co-operation. A couple of weeks ago this seemed a given. Today, that this is so much less certain is remarkable in itself. And finally we encourage excellence in science. Excellence comes in many forms – academic excellence is just one, and usually insufficient on its own to be good for much. We put forward the idea that in this age, everyone is a scientist – or part of the science ecosystem. This doesn’t mean everyone has to read up on Rutherford and Salk, but rather they everyone should be able to value – and be able to participate in – the search for truth and understanding. Stevens comments: ‘There are so many, many challenges facing our species. Population, climate, equality, health, environment and more besides. It’s one thing to make science struggle to support and justify its activities – that is only appropriate. It is quite another to actively hunt it down and tear down truths.’ Late last year the NZAS chose to target the theme of science in society, for 2017. What we didn’t realize was that this was going to become street-warfare. In the coming months there will be global demonstrations (in NZ see @ScienceMarch_NZ on twitter). This is not just scientists protesting about science funding – it is about the serious consequences for all of us if science – and other forms of scholarship – are ignored and undermined. 2017 is also an election year and a time when we need to support the values we want for the future. The comfort some of us are lucky enough to experience in NZ naturally enough drives complacency. But the time for complacency has passed. If you think science is apolitical, then ask yourself whether you also believe science can work under all political regimes.